Effect of Porosity and Buoyancy Ratio Parameter for Aiding and Opposing Flows in MHD Stokes Problem in Porous Medium: Understanding Fluid Flow in Porous Media (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Stream, warmth and mass exchange driven by lightness, in permeable media has been concentrated broadly lately. This is because of the expanding need in understanding the confounded vehicle measure for use of different fields, which incorporates mathematical designing, building protection, energy preservation, strong framework heat exchangers, filtration interaction, and underground removal of atomic waste materials. Liquid move through permeable media is experienced in various parts of science and designing, going from horticultural, compound, common and oil designing, to food and soil sciences.